Edukasi terhadap Sikap Upaya Pencegahan Komplikasi pada Penderita Hipertensi (Journal of Telenursing (JOTING), 2024)
The aim of this research is to determine the effect of educational activities on the attitudes of hypertension sufferers in carrying out preventive measures against the possibility of complications. This research method uses a pre-experimental approach with a pre-test and post-test design in one group. The results of the study showed that the average attitude towards preventing complications in hypertension sufferers before education was 25.13 and after education increased to 35.97. Analysis using the Wilcoxon Test shows a probability value (p) of 0.001, indicating p